IMPROVEMENT OF THE WORKING CAMERA OF THE DV-1M ROLLER DEVICE EQUIPMENT (Journal of Science-Innovative Research in Uzbekistan, 2024)
The principle of operation of the air conveying device is that the atmospheric air, under the flow created due to the pressure difference, pushes the material being transported along with it into the pipe.The cotton moves in absolute condition in the pipe and reaches the separator